Bisphenol A (BPA) in liquid portions of canned foods obtained from domestic and Asian markets in the United States - Aby Joiakim; David Kaplan; David A Putt; Julia Matzenbacher Santos; Klaus Friedrich; So Hee Kim; Hyesook Kim (Wolters Kluwer Medknow Publications, 2019)
Bisphenol A (BPA) is a phenolic environmental estrogen that disrupts endocrine activity thereby increasing the risk of hormone-related health problems. The human population is highly exposed to BPA and food is believed to be a primary source of BPA exposure. The aim of this study was to test the sensitivity and specificity of a BPA enzyme-linked immunosorbent assay (ELISA) and to measure levels of BPA in supernatants obtained from various canned foods from different countries. The concentration of BPA was measured in supernatant from different types of canned soup and vegetable mixes produced by US companies and two companies each from three different Asian countries (Korea, Japan and China), which are available at markets in the USA. ELISA results were confirmed by LC/MS/MS and shown to be in agreement. Cross-reactivity tests demonstrated that BPA ELISA kit does not cross-react with other tested phenolic compounds. There was no significant difference of BPA levels in different types of soups from different US companies. However, levels of BPA in supernatants of canned vegetable mixes of a company in the USA were 200-fold lower than the levels in canned vegetable soups of the US companies. BPA levels varied greatly among canned foods among companies in various countries. Thus, this study validated the use of a simple ELISA assay to measure levels of BPA in supernatants of canned food, which would facilitate the routine monitoring of dietary exposure to BPA. Decreasing the consumption of BPA will lead to a reduction in the risk of adverse health effects.